Assessing Human Needs - Jones, John (Philosophy & theology, 1990)
This paper investigates the meaning of needs claims to determine conditions under which they can be falsified. Interpreting needs as necessary requirements, I consider two distinct versions of the statement “A needs X.” One is hypothetical: “If A is to do or obtain Y, then A needs X.” The other is categorical - “A needs X at hand” - and is derived from the hypothetical statement when A is in some manner to do Y. I argue that, despite some cases in which needs claims cannot be falsified, formal criteria can be adduced to falsify or, at least, challenge both versions of needs claims.